Increasing Natural Resources, Fiscal Policy, and Political Stability on Regional Growth and Economic Resilience - Baehaqi; M Amin (Institut Bisnis dan Informatika Kesatuan, 2025)
Growth and resilience economy become an issue strategically in development areas, especially in the Province of West Nusa Tenggara/Nusa Tenggara Barat (NTB). This study aims to analyze the influence of the source of Power and nature, fiscal policy, and political stability on regional growth and economic resilience in West Nusa Tenggara Province. This research employs a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Respondent in the study is the apparatus government area, perpetrator business, and figures a society that understands management source nature, policy fiscal, and stability politics. Research results show that natural resources are positively influential and significant to regional growth and economic resilience, emphasizing the importance of managing local resources optimally and sustainably. Policy fiscal influence is significant to regional growth through effective budget management, but​ has not yet had a significant impact on the resilience of the economy. Stability and politics have become the most dominant factors in pushing regional growth and strengthening the resilience of the economy, with the creation of a certainty law, and a climate conducive to investment.